2013
DOI: 10.1109/jdt.2012.2226205
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Nitride-Based Light-Emitting Diode With a Thin Mg-Delta-Doped Hole Injection Layer

Abstract: The performance of InGaN/GaN multiple quantum wells (MQWs) blue light-emitting diodes (LEDs) was improved by inserting a thin Mg-delta-doped hole injection layer at the end of the MQWs. The forward-and reverse-leakage currents were significantly reduced compared with those of the LEDs without the inserting layer. The light output power was enhanced by 13% at a 350 mA injection current. The improved performance could be ascribed to the dislocation suppression and hole concentration enhancement in the p-type GaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…[9,10] The introduction of a Mg-delta-doped hole injection layer has also been proposed to improve the hole doping efficiency of the p-type layer, thereby enhancing the light output power. [11,12] On the other hand, as many scholars have reported, [13][14][15] there are periodically varying electric fields in the short-period superlattice electronic barrier layer compared to the conventional electronic barrier layer, which can result in periodic variation of the energy band. And the conduction band barrier height is raised, suppressing the electron leakage into the p-type region, while the valence band barrier height is reduced, promoting the hole injection active region.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The introduction of a Mg-delta-doped hole injection layer has also been proposed to improve the hole doping efficiency of the p-type layer, thereby enhancing the light output power. [11,12] On the other hand, as many scholars have reported, [13][14][15] there are periodically varying electric fields in the short-period superlattice electronic barrier layer compared to the conventional electronic barrier layer, which can result in periodic variation of the energy band. And the conduction band barrier height is raised, suppressing the electron leakage into the p-type region, while the valence band barrier height is reduced, promoting the hole injection active region.…”
Section: Introductionmentioning
confidence: 99%
“…To improve hole injection, P-GaN, AlGaN, InGaN, and InGaN/GaN superlattices were used as hole injection layers, [17][18][19][20][21][22][23] Shur et al, [24] and Chitnis et al [25] showed that an accumulation hole layer (AHL) can be created at Al-GaN/GaN interface in AlGaN/GaN heterostructure by using polarization effect. In the present paper, we propose a ptype InAlGaN hole injection layer (HIL) which also acts as a stress release layer (SRL) [26] between the multiple quantum wells (MQW) and the AlGaN electron blocking layer (EBL) for InGaN/GaN blue light-emitting diode (LED), which probably enhances the hole injection without lowering the blocking capability of electrons and improves the radiation and luminous efficiency.…”
Section: Introductionmentioning
confidence: 99%